On the multiplier rules. (3rd May 2016) - Blot, Joël
Abstract : We establish new results of first-order necessary conditions of optimality for finite-dimensional problems with inequality constraints and for problems with equality and inequality constraints, in the form of John's theorem and in the form of Karush–Kuhn–Tucker's theorem. In comparison with existing results, we weaken assumptions of continuity and of differentiability.